WEIGHT CHANGES AND HISTOLOGY OF TESTES OF MALE WHITE RATS (RATTUS NORVEGICUS) DUE TO PROVISION OF RED GUAVA LEAF (PSIDIUM GUAJAVA L.) LEAVES - Sripratiwi, Chessy (Fakultas Kedokteran Universitas Sriwijaya, 2019)
Red Guava Leaf (Psidium guajava L.) is a plant that grows in Indonesia. Chemical content contained in red guava leaves are alkaloids, flavonoids, tannins, essential oils and beta-sitosterol which are thought to be antifertility. As the population increase is very high at 1.49% per year, it is necessary to develop a contraceptive method in men that is safe, effective and high reversibility. The aim of this study was to analyze the changes in testicular weight and histology of male white rats (Rattus norvegicus) due to the administration of red guava leaf fraction. The research method used was true experiment with post test control group design using 24 male rats divided into 4 treatment groups, each group consisting of 6 male rats. Each group was treated with n-hexane, ethyl acetate, methanol water as much as 80 mg / head / day for 48 days and for the control group was given 1% 2 ml CMC, administered by oral sonde. The results showed an average decrease in testicular weight, seminiferous tubule diameter, thickness of the seminiferous tubular epithelium and a decrease in the number of Leydig cells between the control group and the treatment group. Testicular weight and diameter of the seminiferous tubules in the post hoct test results between the control group and the treatment group obtained p value <0.05 means that there is a very significant difference in thickness of the seminiferous tubular epithelium between the control group and the treatment group. Likewise on the thickness of the seminiferous tubule epithelium and the number of Leydig cells, the results of the post hoct test showed a p value <0.05. From the results of this study it can be concluded that the fraction of red guava leaves can reduce the weight of the testes, the diameter of the seminiferous tubules, the epithelial seminiferous tubules and the number of Leydig cells.